Zwingli and the Anabaptists: How Friends Became Enemies - Leu, Urs B. (Reformed theological review, 2024)
In Zurich, two Reformation churches emerged within a few years, both of which can be traced back to Huldrych Zwingli and his associates: the Reformed Church and a branch of Anabaptism, from which the Amish and Mennonite churches emerged. While Zwingli advocated a Reformed state church, the Anabaptists pleaded for the founding of a free church that would put into practice what was recognized as right from the New Testament, regardless of political sensitivities. The latter was so contrary to the self-image of the Zurich state that it led to serious conflicts with Zwingli and the authorities.